Isolation And Diagnosis Of Skin Fungi That Causes Tinea Capitis In The Children - Sarah omran Rasheed; Mohammed Sami Farhan; Sarah Hashim Oubid (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
One hundred clinical samples of hair and scalp flakes were collected for children with tinea capitis aged from 1 year to 12 years from the dermatology consultant affiliated with Tikrit Teaching Hospital and outpatient clinics, with the aim of isolating the pathogenic fungi that cause tinea capitis and diagnosing them in children. Out of the total, 77 samples were found in the laboratory culture, while the findings of the direct microscopic examination indicated the presence of 55 samples. Several dermatophyte species from the genera Trichophyton and Microsporum were identified. T. mentagrophytes was the most prevalent with 18 isolates (23%), followed by T. violaceum and T. rubrum, each with 12 isolates (15%). Next, there were 10 isolates of the fungus T. schoenleinii (13%), compared to 4 isolates (10%) of each of the two species of fungus, T. tonsurans and T. verrucosum. While fungi belonging to the genus Microsporum were isolated at a rate of 10 isolates (13%) of the type M. canis, while 7 isolates of the M. gypsum type were isolated (9%). The incidence of tinea capitis among was greater in men than in women., as the number of infected males was 62 (62%), and females were 38 (38%) infected out of the total number. Regarding age groupings, 20% of children between the ages of one and four have head ringworm. The infection rate for children aged 5-8 was 32%, and the highest risk of infection was for those aged 9-12, who were at risk for 48%. It was also found that the rate of infection with the fungi that cause tinea capitis in the children from whom the samples were taken was high among patients coming from rural areas, at 80%, compared to patients coming from urban areas, at 20%.